Critical thinking and learning of mathematics in incoming college students - Campos-Fabian, Diana Ruth (2020)
The 21st century requires people to make good decisions based on thoughtful and reasoned thinking. It is the task of the university teacher to provide the necessary conditions to develop critical thinking by using strategies that place the student as the basis of teaching work. The objective of the research was to determine the relationship between the level of critical thinking and the level of learning of mathematics of students entering university. The research is based on the quantitative correlational scope approach with transectional, correlational design. The sample was 115 students belonging to two universities, one private and the other public, located in Lima, Peru. For data collection, two tests were administered: one to assess the level of critical thinking, and the other to assess the level of learning in mathematics. The results show that critical thinking and learning of mathematics are significantly correlated. Likewise, each dimension of mathematics learning is significantly correlated with critical thinking. It is concluded that critical thinking favors the learning of mathematics in students entering university. This research serves as an indicator for mathematics teachers to use teaching strategies that develop critical thinking at the university level to obtain better results in learning mathematics.